On Peppa Pig’s Method - Mangiapane, Francesco (E|C, 2022)
This article goes through the events and the theoretical problems raised by the publication of a Semiotic essay that the author has dedicated to the analysis of Peppa Pig, a popular TV series targeted to early-childhood. Assuming a situated point of view, it chooses to dramatize the position of the researcher towards the complexity as represented by the emergence of the “wilderness” of the text to analyze. Consequently, this article aims at enlightening the strategies actually followed by the author in facing this complexity. What format and style to choose in the writing process? How to identify the limits of the text? How to evaluate the eventuality that inspired the analytical curiosity into a wider cultural context of discursivity as staged by Early-Childhood cartoons? By providing a local response to these general problems, the article presents itself as a Discourse on Method, in which are assessed the diverse issues faced by the analyst committed with the practice of an actual Semiotic Analysis. Prepensely, the article will result into a philosophical enquire on how a proper Semiotic Analysis gets substantiated.